PENGGUNAAN MODEL STAD BERBANTUAN MEDIA INTERAKTIF CANVA UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS 4 SD MUHAMMADIYAH ABEPURA TAHUN AJARAN 2025/2026 - Isyaria; Suwita; Yuliana, Chelsi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted in response to the relatively low learning outcomes and classroom participation of fourth-grade students in the Science and Social Studies (IPAS) subject at SD Muhammadiyah Abepura. These conditions were associated with the dominant use of conventional teaching methods and the limited use of interactive learning media. The study aimed to improve students’ cognitive achievement and learning participation in the Global Warming topic through the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model supported by Canva interactive media. The research employed Classroom Action Research (CAR) based on the model of Kemmis and McTaggart and was carried out in two cycles. The participants consisted of 20 fourth-grade students. Data were collected through learning outcome tests, observation of student activities, and documentation. The findings showed a clear improvement in students’ learning mastery. Classical completeness increased from 35% in the pre-cycle to 70% in the first cycle, and reached 85% in the second cycle. In addition, the integration of the STAD model with Canva media contributed to more active participation, greater confidence in expressing ideas, and stronger cooperation among students. In conclusion, the application of the STAD learning model assisted by Canva interactive media was effective in improving both the learning process and the IPAS learning outcomes of elementary school students.